Life cycle assessment : principles, practice, and prospects - Horne, Ralph, 1966- (CSIRO Pub., 2009)
Life Cycle Assessment (LCA) has developed in Australia over the past 16 years in a fragmented way with many different people and organisations contributing to the area at different times, and largely through informal or unpublished work. This publication will legitimise and document LCA research and methodology development to act as a record of what has happened and a basis for future development and application of the tool.
Keywords: Environmental impact analysis -- Australia.; Life cycle costing -- Australia -- Methodology.; elektronické knihy; electronic books